Ocorrência, distribuição espaço-temporal e flutuação da população de percevejos pentatomídeos em sucessões culturais sob pivô central e áreas adjacentes - Aguero, Marcos Arturo Ferreira (2010)
The stink bugs are pests of soybean, corn, wheat and other crops. Economically, its management and key knowledge and behavior of their populations are needed to plan effective of action. The objective of this research was to investigate the occurrence, spatial-temporal distribution and population fluctuations of species of stink bugs in the succession of crops. The study was conduced during 12/2007 to 11/2009 on Jóia, RS, Brazil, in a commercial farming area of 162ha with no-tillage system, and center pivot irrigation (92ha) and adjacent areas (70ha). In the first year of study, 2007/08, 41ha pivot was planted with soybean [Glycine max (L.) Merrill] and 51ha, with corn (Zea mays L.), while in the offseason of 2008, with 41ha oat (Avena strigosa Schreb) associated with wild radish (Raphanus sativus L.) in succession to soybean and 51ha with oat in corn stubble. In the second year, the 2008/09 crop was planted soybeans in the entire pivot area (92ha) and adjacent areas (70ha). Already in the 2009 offseason, was season black oat (Avena sativa L.) in succession to soybean and wheat (Triticum aestivum L.) in the areas adjacent. Through the Campeiro CR-6® Software was generated a thematic map of the research and divided into regular grid of 63 cells 2.5 ha and their centers constituted the sampling points. The points were located with GPS. Samplings were made fortnightly in 2m², surveying vegetation, straw, crop residues and soil surface. Was noted the number of bugs nymphs from second instars and adults. The species were confirmed in the laboratory of Integrated Pest Management (LabMIP).To analyze the occurrence of population were used statistical series of geographical and temporal, is drawing up tables of frequency distribution of the population for each culture of the pivot, surrounding areas and places of refuge. The data were statistically analyzed by software BioEstat5®. We applied the binomial probability test between the populations of stink bugs on crops and surrounding areas to verify the differences in 0.05 level of significance. To analyze spatial and temporal distribution, we used the CR-Campeiro6 ® generating digital maps of population distribution of stink bugs. To analyze the fluctuation, graphics were elaborated through the Excel® Software. Was quantified the populations of Euschistus heros (Fabricius, 1798), Dichelops furcatus (Fabricius, 1775), Piezodorus guildinii (Westwood, 1837), Nezara viridula (Linnaeus, 1758) and Edessa meditabunda (Fabricius, 1794). During the two years of study, E. heros and D. furcatus was the species most frequent in soybeans. D. furcatus is more common in corn, wheat and oats. P. guildinii occurs frequently in soybeans. Populations of N. viridula and E. meditabunda are less frequent. In the offseason, the bugs shelter in the trash, weeds, wheat, oats, turnip and migrate to the edge of forest vegetation and wetland. Populations of stink occur more frequently in soybean at stage R7.1 and R9, corn in summer and winter grasses. The location of the beginning of planting determines the distribution of the population. Areas sown late have high immigrant populations of bugs crop more developed or already picked. The occurrence, spatial-temporal distribution and population dynamics of stink bugs vary each year, influenced by soybeans, corn, wheat, oat, turnip, the crop successions, culture adjacent, alternative host plant, trash, weeds and management operations.